Flexible fluoroscopes. Issue 5 (20th January 2020) - Balter, Stephen
Key Points: Different fluoroscopes have various controls that influence radiation output and clinical image quality. "Standard" settings often result in relatively high radiation output as a way of producing image quality is high enough almost all procedures. Operator knowledge of the characteristics of individual fluoroscopes is an essential element of radiation reduction below "standard settings" without reducing clinical benefits.